PERIPHERAL ARTERY REMODELLING AS ENDOTHELIAL DYSFUNCTION PREDICTOR IN PATIENTS WITH ARTERIAL HYPERTENSION AND ABDOMINAL OBESITY - N. N. Molchanova; I. A. Zagretdinov; A. M. Teregulova; L. N. Mingazitdinova; E. G. Mutalova; L. B. Novikova (Российский кардиологический журнал)
The stiffness, elasticity, and endothelial vasodilatation of common carotid artery (CCA), femoral artery (FA) and renal arteries (RA) were examined in 60 patients with arterial hypertension (AH) and obesity, as well as in 20 patients with essential AH (EAH). Comparing to EAH individuals, patients with AH, obesity and insulin resistance (IR) demonstrated reduced elasticity, increased stiffness and early atherosclerotic changes in CCA and FA. Peripheral artery stiffness depended on AH stage, duration and blood lipids. Endothelial dysfunction was linked to metabolic disturbances, as demonstrated by a significant correlation between immuno-reactive insulin (IRI) and reactive hyperemia test for brachial artery (r=-0,238; p=0,04).